The spatial-temporal and coordinative structures in elite male 100-m front crawl swimmers - Seifert, L.; Boulesteix, L.; Carter, M.; Chollet, D. (International Journal of Sports Medicine, 2005)
This study analysed the spatial-temporal and coordinative structures in 12 elite male 100-m front crawl swimmers. Swim performance was analysed over each length of a 25-m pool divided into five zones of 5 m. Velocity (V), stroke rate (SR), and stroke length (SL) were calculated for each zone and each length. Four stroke phases were identified by video analysis and the Index of Coordination (IdC) was established. Three modes of coordination were identified: catch-up (IdC < 0), opposition (IdC = 0), and superposition (IdC > 0). The swimmers tended to reduce the decrease in V and SR over the course of the 100 m by maintaining a stable SL. In fact, these spatial-temporal values were stable during the time spent stroking and were higher or lower during the start, the turns (in and out), and the finish. Thus the spatial-temporal changes did not occur within the lengths, but between them. Conversely, the evolution in the IdC showed that the swimmers had to install the stroke at the beginning and only reached a stable coordination in the second part of the race. Moreover, the IdC increased throughout the different zones of each 25-m length, indicating changes in motor organisation, particularly increases in the push or pull phases. The IdC values corresponded to a superposition of the arms, linked to a six-beat leg kick. Achievement of an effective superposition coordination occurred by boosting the stroke just after the turn-out until the end of the length. Regarding the spatial-temporal and coordinative structures of a 100-m front crawl, great swimming skill was reflected by both high and stable data.